When Ancient Lithuanian State Became an Empire and Ceased to Be It? An Answer to Lithuanian Question Using an Estonian Method - Norkus, Zenonas (Lietuvos istorijos studijos, 2009)
The article introduces a Lithuanian reader into the ideas of distinguished American-Estonian political scientist Rein Taagepera on comparative cliometrics of empires and uses them to detect main thresholds in the imperial history of ancient Lithuania. For this goal, its size-time integral (called in the paper Taagepera integral) was measured. It is used to calculate the maximum stable size (M), emergence (20% of M), adulthood (80% of M), failure (50% of M) dates, rise and duration times of the ancient Lithuanian empire. According to author's calculations, ancient Lithuania emerged as an empire already under Mindaugas rule (before 1263), and its rise time was about 100 years. Its adulthood came in the early sixties of the XIV century, and it failed in 1569, when just before the Lublin Union, Poland annexed the southern provinces of the Grand Duchy of Lithuania. So its duration time was slightly more above 200 years. These chronological conclusions are made under the assumption that the old Lithuanian state survived until 1795. If this assumption is exchanged for another that says that 1569 was also the endpoint of the ancient Lithuanian state, only slight changes are to be made in these conclusions.
Keywords: -